RETRACTED: Research of improving the method of designing ergonomic clothing for special purpose, taken into account of the construction of the “armholesleeve” unit - Yunusxodjaeva Khayrinisa; Vakhidova Umida; Yunusxodjaeva Nilufar (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001